Efgartigimod in the treatment of Guillain-Barré syndrome: case report - Deng, Min; Kong, Zhaohong; Wang, Yan; Wang, Xufeng; Li, Tao (Frontiers in Immunology, 2025)
Guillain–Barré syndrome (GBS) is a rare neurological disorder characterized by muscle weakness and paralysis. Although the exact etiology remains unclear, the current standard treatments include intravenous immunoglobulin (IVIG) and plasma exchange (PLEX) therapy. While the majority of GBS patients respond well to immunotherapy, some severe cases can be fatal. Efgartigimod, an Fc receptor antagonist, has been utilized in the treatment of various autoimmune diseases. However, its clinical efficacy in acute GBS has been rarely documented. In this study, we administered intravenous efgartigimod to four patients with different subtypes of acute GBS, two of whom received efgartigimod monotherapy without concomitant glucocorticoids, IVIG, or PLEX. The treatment outcomes were favorable, suggesting that intravenous efgartigimod may represent a promising therapeutic option for acute GBS. Further research is warranted to validate these preliminary findings.